Relevance of Macrophage Extracellular Traps in C. albicans Killing - Loureiro, Ana; Pais, Célia; Sampaio, Paula (Frontiers in Immunology, 2019)
Candida albicans causes systemic life-threatening infections, particularly in immunocompromised individuals, such as patients in intensive care units, patients undergoing chemotherapy, and postsurgical and neutropenic patients. The proliferation of invading Candida cells is mainly limited by the action of the human innate immune system, in which phagocytic cells play a fundamental role. This function is however limited in neutropenic patients, who rely mainly on the protective immunity mediated by macrophages. Macrophages have been shown to release extracellular DNA fibers, known as macrophage extracellular traps (METs), which can entrap and kill various microbes by a process called ETosis. In this study, we observed that, upon contact with C. albicans, macrophages became active in phagocyting and engulfing yeast cells. ETosis was induced in 6% of macrophages within the first 30 minutes of contact and this percentage increased with the multiplicity of infection until a plateau was reached. After 2.5 hours of incubation, the presence of extracellular macrophage DNA was observed in approximately half of the cells. This study suggests that the formation of METs occurs before pyroptosis (first 6 to 8 hours) and macrophage cell death (up to 24 hours) and thus METs could be included in models describing C. albicans: macrophage interactions. We also observed that macrophage ETosis and phagocytosis can occur simultaneously and that in the first hours of infection both processes are similarly important in controlling the proliferation of yeast cells, this being critical in neutropenic patients. Finally, it can also be concluded that, since C. albicans can degrade DNA, the structural component of METs, yeast extracellular DNase activity can be considered as an important virulence factor.